2022
DOI: 10.1161/circinterventions.121.011612
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Culprit Plaque Characteristics Among Different Age Groups in Patients With Acute Coronary Syndromes

Abstract: Background: Despite the significant decline in cardiovascular mortality in women over the past several decades, sex differences in the underlying pathology of acute coronary syndromes remain poorly understood. Previous postmortem studies have demonstrated sex differences in coronary plaque morphology with a higher prevalence of plaque erosion in young women and more plaque rupture in older women after menopause, whereas men showed no increase in prevalence of plaque rupture with age. However, in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…33 Plaque erosion has been identified as the dominant underlying pathology in young women with ACS. 12,13 Plaque Instability and Plaque Healing…”
Section: Layered Plaque and Clinical And Angiographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Plaque erosion has been identified as the dominant underlying pathology in young women with ACS. 12,13 Plaque Instability and Plaque Healing…”
Section: Layered Plaque and Clinical And Angiographic Characteristicsmentioning
confidence: 99%
“…Women show less obstructive coronary artery disease on angiogram, and plaque erosion has been found more frequently in younger women. 11–13 Moreover, men with ACS exhibited significantly higher levels of pericoronary adipose tissue attenuation at the culprit plaque and all 3 major coronary arteries levels, indicating a higher level of vascular inflammation. 14 Postmortem studies in men showed a higher prevalence of disrupted pattern in healed plaques, suggesting previous plaque ruptures as a predominant mechanism for plaque progression in men.…”
mentioning
confidence: 98%
“…An autopsy study showed that women had a greater frequency of plaque erosion and distal microvascular embolization, as well as a greater rate of embolization independent of thrombus type or presence of necrosis, than men [31,32]. A recent study showed that plaque rupture and vulnerability increased with age in women but not in men [33].…”
Section: Discussionmentioning
confidence: 99%
“…12 Regarding the latter, differences are observed in plaque composition, vulnerability, and burden between men and women, pointing toward a respectively more atheromatous versus fibrous phenotype. [13][14][15] The plasma proteome reflects the dynamic biological state, which, prior to disease, may provide insight into the mechanisms of (sex-specific) CAD onset. The UK Biobank is a largescale biomedical healthcare database comprising population-scale data of 2,922 unique plasma proteins in 54,219 individuals.…”
Section: Introductionmentioning
confidence: 99%